Field- and laboratory-derived determinants of performance in sprint cross-country skiing: time-trial versus final performance - Brattebo, J.-M. (Norwegian University of Science and Technology, 2022)
Purpose: To investigate field- and laboratory-derived determinants of performance in a sprint cross-country skiing (XCS) competition. Since the time-trial (TT) in sprint XCS has previously been well researched and there is limited knowledge of the knockout heats, a secondary aim was to compare the magnitude of the associations between determinants and performance in the time-trial and overall competition. Methods: Seventeen male junior athletes (age: 18.5 ± 0.8) competing on a national level performed a simulated sprint XCS competition, including a TT and four knockout heats, followed by the tests; (1) 5-min submaximal stages and an incremental test to exhaustion while treadmill G3 skating to determine peak oxygen uptake (VO2peak) and gross efficiency (GE); (2) maximal strength (1RM) in pulldown and triceps press, 1RM and peak power (PP) in leg press, and a 30-s Wingate double poling test; and (3) maximal velocity (Vmax) tests in flat and uphill terrain on snow. Spearman`s rank-order correlation (rS) and multiple regression analysis explored the relationship between TT-rank and final rank in the XCS competition versus laboratory-, and field-based test-results. Results: Strong correlations were found between Vmax flat and VO2peak (L/min) and both TT-rank (rS= 0.75 and 0.70; both p< 0.01) and final rank (rS= 0.86 and 0.80; both p< 0.01). Leg press PP, 1RM triceps press and GE also showed strong and moderate correlations to the final rank (rS= 0.76, 0.60 and 0.54; all p< 0.05). Comparing the magnitude of associations between determinants and rank in the TT and final, found Vmax flat and 1RM triceps press to be DeltarS > 1.5 SD (p= 0.07 and 0.06), with moderate effect size (q= 0.32 and 0.28). Together, Vmax flat, GE and 1RM triceps press explained ~97% of variance in final rank. Conclusion: Vmax and VO2peak (L/min) are the two greatest determinants of performance in junior sprint XCS. The same determinants that were associated with TT-rank were more strongly associated with final rank. Furthermore, determinants that were not found to be significantly associated with TT-rank, were so with the final rank, in which the effect of the changes ranged from moderate to small. The influence of known determinants of performance appears to be different in a single time-trial vs a competition event and aerobic and anaerobic power seem to be essential in achieving a high rank in a sprint XCS competition